A rigorous analysis of the distribution of power in plastic clad linear tapered fibers - YEOW, S; LIM, M; CHOUDHURY, P (2006)
An analytical investigation is presented of the propagation of power in a step-index plastic clad tapered optical fiber operating in the infrared region of the electromagnetic (EM) spectrum. The chosen materials are widely used in low cost optical links. It is assumed that the taper section has a linear profile. Following rigorous analytical approach, the general expressions for power in the core and the cladding sections are derived, and a study 1:3 presented of the variation of the relative power along the propagation direction in respect of different (meriodinal and skew) lower order modes. It is observed that, in general, the confinement of power is fairly high in the core section, and the confinement increases with the increase in the taper length and/or mode index. In the cladding region, the confinement decreases for higher taper lengths. (c) 2005 Elsevier GmbH. All rights reserved.